PEMBENTUKKAN KARAKTER PESERTA DIDIK MELALUI PEMBELAJARAN MONTESSORI: PEMBENTUKKAN KARAKTER PESERTA DIDIK MELALUI PEMBELAJARAN MONTESSORI - Suwarno Putri, Yuriska Dewi (AL-IHTIRAFIAH: JURNAL ILMIAH PENDIDIKAN GURU MADRASAH IBTIDAIYAH, 2021)
Abstract Character building is believed to be necessary and important for schools to do. The purpose of character education is basically to encourage the birth of good children (insan kamil). The growth and development of good character will encourage students to grow with their capacity and commitment to do the best things and do everything right and have a purpose in life. Montessori learning can shape the character of students starting from the smallest things, namely discipline and responsibility for each task given by the teacher. This research uses qualitative research with data collection techniques of observation, interviews, and documentation which are then tested using data triangulation. The results showed that by applying Montessori learning can help students to form a positive character.